PENGARUH PEMBELAJARAN BERDIFERENSIASI BERBASIS PROJECT BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA KELAS V DI UPT SPF SD INPRES KARUNRUNG - Ainun Jumriatillah; Sayidiman; Abdul Rahman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was motivated by the low creative thinking abilities of students in Mathematics. The research aimed to describe the implementation of differentiated learning based on Project Based Learning (PjBL), students’ creative thinking abilities, and the effect of this approach on fifth-grade students at UPT SPF SD Inpres Karunrung. The study used a quantitative approach with a Quasi-Experimental Nonequivalent Posttest-Only Control Design involving 42 students. Data were collected through observations and pretest–posttest assessments.The observations showed an improvement in learning implementation from the good to the very good category. In the experimental class, pretest scores were in the less creative category, while posttest scores increased to the highly creative category. The Shapiro–Wilk normality test indicated that the data were normally distributed, and the One-Tailed Independent Sample T-Test revealed a significant difference between the experimental and control classes. Thus, differentiated learning based on PjBL positively influenced students’ creative thinking abilities.